1988
DOI: 10.1111/j.1365-2257.1988.tb00021.x
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of chronic idiopathic thrombocytopenia with anti-D (Rho) immunoglobulin: its effectiveness, safety and mechanism of action

Abstract: Twenty-three courses of i.v. anti-D (Rho) immunoglobulin were administered to 13 Rh D-positive patients with chronic idiopathic thrombocytopenia (ITP). Clinically significant responses were seen in a proportion of patients treated with 500-2500 i.u. anti-D, but all those treated with 12,500 i.u. (180 i.u./kg) responded. Patients refractory to other forms of treatment responded well to anti-D, and previous splenectomy did not influence the clinical response. No adverse reactions were observed. The anti-D respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…27 Several studies have confirmed that anti-RhD is an effective and safe treatment option in ITP. 28,29 Moreover, similar to IVIG, this agent has the benefit of inducing a more rapid increase in platelet count than oral corticosteroids; however, it also requires intravenous infusion and usually demonstrates a infection did not influence the response to the treatment among the adults. The response rate in the adult group was 72% and was significantly higher in patients with hemoglobin levels ≥12 g/dL.…”
Section: Anti-rhd Formulationsmentioning
confidence: 99%
“…27 Several studies have confirmed that anti-RhD is an effective and safe treatment option in ITP. 28,29 Moreover, similar to IVIG, this agent has the benefit of inducing a more rapid increase in platelet count than oral corticosteroids; however, it also requires intravenous infusion and usually demonstrates a infection did not influence the response to the treatment among the adults. The response rate in the adult group was 72% and was significantly higher in patients with hemoglobin levels ≥12 g/dL.…”
Section: Anti-rhd Formulationsmentioning
confidence: 99%
“…These studies provide valuable information about RhIG in mismatched transfusion inasmuch as they illustrate treatment tolerability. The early studies involved a wide range of doses and administration regimens 48‐53 . Based on earlier work to establish PLT‐sparing efficacy, the total RhIG doses given in these studies were relatively high compared to those used in D‐mismatched transfusion.…”
Section: Lessons From Immune Thrombocytopenic Purpuramentioning
confidence: 99%
“…The early studies involved a wide range of doses and administration regimens. [48][49][50][51][52][53] Based on earlier work to establish PLTsparing efficacy, the total RhIG doses given in these studies were relatively high compared to those used in D-mismatched transfusion. Experiences with these doses are therefore likely to exaggerate the adverse events associated with RhIG administration.…”
Section: Lessons From Immune Thrombocytopenic Purpuramentioning
confidence: 99%
“…88 "" 93 Other investigators reported similar results. [94][95][96][97][98][99][100] The same approach has been used for treating HIV-related thrombocytopenia in D+ patients. 98 < 10°-i°3 In about 25% of D+ patients, Rh(D) IVIgG therapy does not seem effective.…”
Section: Anti-dmentioning
confidence: 99%